2003
DOI: 10.1016/s0378-5955(03)00073-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic material properties of the tectorial membrane: a summary

Abstract: Dynamic material properties of the tectorial membrane (TM) have been measured at audio frequencies in TMs excised from the apical portions of mouse cochleae. We review, integrate, and interpret recent findings. The mechanical point impedance of the TM in the radial, longitudinal, and transverse directions is viscoelastic and has a frequency dependence of the form 1/(K(j2pif)(alpha)) for 10 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 60 publications
5
32
2
Order By: Relevance
“…While previous studies have demonstrated the importance of TM stiffness in cochlear mechanics [2,3,5,6,13,15], our results suggest that shear viscosity is also an essential material property of the TM. Specifically, our results show 080003-2 that TM stiffness alone cannot explain the hearing phenotypes of Tecta Y1870C/+ and Tectb -/-mutant mice.…”
Section: Importance Of Tm Shear Viscositycontrasting
confidence: 73%
“…While previous studies have demonstrated the importance of TM stiffness in cochlear mechanics [2,3,5,6,13,15], our results suggest that shear viscosity is also an essential material property of the TM. Specifically, our results show 080003-2 that TM stiffness alone cannot explain the hearing phenotypes of Tecta Y1870C/+ and Tectb -/-mutant mice.…”
Section: Importance Of Tm Shear Viscositycontrasting
confidence: 73%
“…However, the TM has been shown to behave as a viscoelastic material (21,27), where its stiffness depends on the rate of stress or rate of strain. We predict that the mechanical differences observed in our pseudostatic measurements will be enhanced in dynamicmechanical measurements conducted under physiologically relevant conditions, i.e., in the functional auditory frequency range at nanometer amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major shortcomings of these studies is the nonphysiological large-scale displacements (tens of microns) that were used to characterize TM properties. Recently, Freeman et al (21) measured the stiffness of isolated mouse TM samples, during submicrometer displacements, using magnetic beads having a diameter of 10 m. More recently, the shear modulus of TM samples isolated from guinea pigs was probed with an atomic force microscope (AFM) using nano-and microscaled indenters (Ϸ20 nm and Ϸ10 m in diameter, respectively) (22). In that AFM study, the mechanical properties of the TM appeared similar as a function of longitudinal position.…”
mentioning
confidence: 99%
“…In another set of experiments, Freeman et al (2003a;2003b) placed a section of mouse TM membrane in a cell-tack coated chamber and vibrated this chamber with a piezo actuator at frequencies between 10 and 14 kHz. At the same time, they recorded the mechanically induced vibrations of the TM with an atomic force cantilever with known mechanical impedance.…”
Section: Tectorial Membranementioning
confidence: 99%